The 1990 Anthrax Outbreak: A Historical Study of the Causes of the Outbreak in the Dairy Perusahaan Inti Rakyat (PIR) Program in Central Java - Nurul Anisyah; Wasino Wasino (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
The implementation of the Dairy PIR Program in Semarang and Boyolali Regencies, the exact cause of which remains uncertain. This study aims to investigate the causes of the outbreak using the historical method proposed by Kuntowijoyo, which consists of five stages: topic selection, heuristics, verification, interpretation, and historiography. The findings indicate that anthrax had existed in Boyolali Regency long before the implementation of the Dairy  PIR  Program, as documented in several colonial newspapers published in 1870, 1879, and 1934. These findings suggest that the source of anthrax infection had been present in the region long before the implementation of the program. Furthermore, the high mobility and density of livestock within the  Dairy PIR Program, combined with an implementation that placed greater emphasis on increasing milk production than on strengthening animal health management, created condition conducive to the spread of the outbreak.